2014
DOI: 10.1016/j.joca.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A new method to measure anatomic knee alignment for large studies of OA: data from the Osteoarthritis Initiative

Abstract: Since it is largely automated and uses unambiguous anatomical landmarks, the new method is highly reproducible and can be made on a standard posteroanterior (PA) knee radiograph by a relatively unskilled reader.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 16 publications
0
70
1
Order By: Relevance
“…Baseline fixed flexion radiographs were used to quantify the new FTA measurement (Version 0.1) [12] and currently, FTA measures are available for the baseline visit only (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Baseline fixed flexion radiographs were used to quantify the new FTA measurement (Version 0.1) [12] and currently, FTA measures are available for the baseline visit only (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…This method does not define FTA by the shaft but utilizes more local information around the joint space and femoral condyles [12][13][14]. The authors reported greater intra-rater and inter-rater reliability [12] for measuring FTA than the traditional method in participants with knee OA, and somewhat greater correlation with HKA (r ¼ 0.75) than for the traditional FTA measurements (r ¼ 0.68). However, the offset between the new FTA measurement methodology and HKA measures has not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations